2018
DOI: 10.1111/bjd.16166
|View full text |Cite
|
Sign up to set email alerts
|

Wet work and healthcare workers: use of hand disinfectants not associated with self-reported eczema

Abstract: Linked Article: Hamnerius et al. Br J Dermatol 2018; 178:452–461.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…A previous study suggested a dose-dependent relationship between hand eczema and handwashing with soap and water as well as the use of disposable gloves among healthcare workers (22). Interestingly, no correlation was noted between the use of disinfectants and the prevalence of hand eczema, indicating the use of disinfectants might be a viable substitute for soap and water handwashing in hand eczema patients (32). Indeed, as shown in a Danish clinical trial, washing hands with disinfectants when there is no visible contamination and moisturizer application improved hand eczema (33).…”
Section: Discussionmentioning
confidence: 92%
“…A previous study suggested a dose-dependent relationship between hand eczema and handwashing with soap and water as well as the use of disposable gloves among healthcare workers (22). Interestingly, no correlation was noted between the use of disinfectants and the prevalence of hand eczema, indicating the use of disinfectants might be a viable substitute for soap and water handwashing in hand eczema patients (32). Indeed, as shown in a Danish clinical trial, washing hands with disinfectants when there is no visible contamination and moisturizer application improved hand eczema (33).…”
Section: Discussionmentioning
confidence: 92%
“…Estudios anteriores han revelado que el eccema de manos es bastante común en los trabajadores de la salud (9,10). En cuanto a los factores de riesgo se incluye la higiene y lavado de las manos con una frecuencia mayor de 10 veces al día, uso prolongado de guantes o de dispositivos de protección terciarios, como máscara N95, gafas, careta y guantes de doble capa (11)(12)(13)(14).…”
Section: Manifestaciones En Piel Secundarias a Uso De Equipos De Protecciónunclassified